Carboplatin-Induced Hypersensitivity Reaction - Evangelos Potolidis; Charalampos Mandros (Case Reports in Oncology, 2012)
We describe a 65-year-old female with relapsed ovarian cancer who developed a severe hypersensitivity reaction during the second cycle of carboplatin treatment. The patient developed respiratory failure, acute respiratory distress syndrome and hypotension, requiring admission to the intensive care unit.